2015
DOI: 10.4103/0019-557x.164656
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for attraction and retention of health workers in remote and difficult-to-access areas of Chhattisgarh, India: Do they work?

Abstract: Establishment of a performance management system, activating the CRMC cell to make it functional, and wide publicity of CRMC benefits are likely to improve attraction and retention of staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…Most commonly reported factors include: inappropriate pre-service training for rural and remote areas practice, lack of prospects for further training and career development, low salaries, poor working environments, limited availability of equipment and drugs, insufficient family support, inadequate management and unsupportive supervision. Although the choice of variables included in this study is guided by the existing literature [34–41], the study could include only a limited number of variables that are available in the DLHS-4 dataset. A detailed description of the variables included in the analysis is given in the table below (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Most commonly reported factors include: inappropriate pre-service training for rural and remote areas practice, lack of prospects for further training and career development, low salaries, poor working environments, limited availability of equipment and drugs, insufficient family support, inadequate management and unsupportive supervision. Although the choice of variables included in this study is guided by the existing literature [34–41], the study could include only a limited number of variables that are available in the DLHS-4 dataset. A detailed description of the variables included in the analysis is given in the table below (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Similar programmes to expand professional training have been conducted in other countries with remote areas. 37 , 38 The need to expand the number of medical courses in Brazil was based on the low supply of undergraduate medical places, which was 0.8 per 10 000 inhabitants in 2011, half that of other countries with universal health systems, such as the United Kingdom of Great Britain and Northern Ireland (1.6 per 10 000 inhabitants). 39 In countries such as Australia, Canada and the United States of America, training programmes to serve populations in remote and rural areas where it was difficult to recruit and retain physicians were implemented in medical schools in the 1960s.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the factors necessary to retain health workers in rural facilities, especially in developing countries, often focused on an increase in pay, on timely payments and other economic benefits for workers (Lisam et al. ; Ojakaa & Jarvis ; Wurie et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies showed that health worker recruitment and retention in rural healthcare facilities could be improved by providing accommodation, special consideration for further studies, financial incentives and providing the necessary work resources (Lisam et al. ; Ojakaa & Jarvis ). In other words, health workers, including nurses, would be more likely to work in rural areas if working conditions were improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation